ENTREPRENEURIAL COMMITMENT SEBAGAI MEDIATOR HUBUNGAN ANTARA ENTREPRENEURIAL SELF-EFFICACY DAN KINERJA BISNIS - Affini, Dinar Nur; Oebit, Cut Edwina Safia (Jurnal Manajemen Sinergi, 2023)
bjective: The goal of this investigation to understand and analyze the relationship between entrepreneurial self-efficacy and commitment and business performance, as well as the function of entrepreneurial commitment as a mediator in that relationship. A total of 250 independent coffee shops are thought to make up the research population. Due to the usage of the Krejcie and Morgan 1970 table, a total of 108 Coffee Shop MSMEs in South Tangerang were included in the research sample.Methodology: The PLS-SEM approach is utilized to analyze the data, and SmartPLS software is employed as tool for statistical testing.Findings: At a 5% level of confidence, the hypotheses H1, H2, and H3 are accepted, and the path coefficient values are positive.Conclusion: The study's findings indicate that: (1) Business Performance is positively and significantly impacted by entrepreneurial self-efficacy. That is to say, self-efficacy Coffee business owners in South Tangerang have faith in their capacity to manage a company and generate financial performance. (2) The performance of a company benefits from entrepreneurial commitment. Inferring that business actors still have a strong desire (commitment) to manage a firm and earn profits, UMKM South Tangerang Coffee Shops' current actions are demonstrably substantiation on respect (3) Business performance is also significantly impacted by entrepreneurial self-efficacy. entrepreneurship dedication. (4) The study's findings also point to the importance of entrepreneurial commitment as a mediator in the relationship between self-efficacy and business performance.